Rhyparographes. - Weemans, Michel (Nantes : Ecole Régionale des Beaux-Arts de Nantes, 1996)
Berchem, Nicolas ; de Bÿje, Marcus ; Bleker, Gerrit ; Fyt, Jan ; Potter, Paulus ; van der Stoop, Dirck ; van Laer, Pieter ; van den Hecke, Jan ; Breughel, P. ; Floris, F. ; Ducq, J. Le ; Bleker, G. ; Heer, J. de Jonck
Rhyparographes, Ecole Régionale des Beaux-Arts de Nantes, 6-30 Mars 1996
Frans
boek